Real-Time Monitoring of Atmospheric Magnesium Alloy Corrosion - Strebl, Michael; Virtanen, Sannakaisa (Journal of The Electrochemical Society, 2018)
The atmospheric corrosion progress of Mg alloys is traditionally tracked by determining mass loss of the samples after exposure. This method provides only an average corrosion rate over the exposure time and is destructive. The work presented introduces a new non-destructive method for real-time monitoring of atmospheric Mg alloy corrosion rates based on the evolved hydrogen gas. This is realized with an adaption of the gravimetric hydrogen collection method. The effect of temperature and atmospheric pressure variations during the experiment can be compensated and reliable atmospheric hydrogen evolution rates can be measured. The new technique was applied to monitor real-time atmospheric corrosion rates of Mg alloys AZ31 and AZ91 with different amounts of NaCl contamination. Comparing the results of the gravimetric hydrogen method with mass loss experiments reveals a good correlation of the consumed charge over the total exposure time, thus validating the new technique. Evidence for the contribution of O2 reduction reaction to cathodic processes on Mg alloy atmospheric corrosion is presented. (C) The Author(s) 2018. Published by ECS.